Size matters: why nanomaterials are different - Roduner, Emil (Chemical Society reviews, 2006)
Gold is known as a shiny, yellow noble metal that does not tarnish, has a face centred cubic structure, is non-magnetic and melts at 1336 K. However, a small sample of the same gold is quite different, providing it is tiny enough: 10 nm particles absorb green light and thus appear red. The melting temperature decreases dramatically as the size goes down. Moreover, gold ceases to be noble, and 2-3 nm nanoparticles are excellent catalysts which also exhibit considerable magnetism. At this size they are still metallic, but smaller ones turn into insulators. Their equilibrium structure changes to icosahedral symmetry, or they are even hollow or planar, depending on size. The present tutorial review intends to explain the origin of this special behaviour of nanomaterials.